Analisis Kepuasan Mahasiswa terhadap Alat Dip Coater Berbasis Mikrokontroler dengan Sistem Kalibrasi Otomatis untuk Pembuatan Lapisan Tipis - Hartanto, Anton; Rahman, Nizar Rizki; Sya'roni, Imam; Prasetyono, Agus Dwi; Subiantoro, Irfan (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Dip coating is a coating method by immersing the material in a solution for a certain time and then removing the material from the dipping place. Dip coating is an effective coating method that adds strength to each coated material and is accurate. Researchers have developed a microcontroller-based dip coater with an automatic calibration system that has 3 main parts, namely the electrical part, the main workspace part, and the power supply part. To determine student satisfaction in using a microcontroller-based dip coater tool with an automatic calibration system that has been developed, an analysis of student satisfaction with the use of the tool that has been developed will be carried out. The purpose of this study was to determine the level of student satisfaction with the microcontroller-based dip coater tool with an automatic calibration system that has been developed. The data collection method in this study was to use a response questionnaire with a Likert scale. The average score of the four indicators obtained a result of 81.78%, which in this case is a very satisfied category. It can be concluded that the student satisfaction index for the Microcontroller-based Dip Coater Tool with an Automatic Calibration System for Making Thin Layers is Very Satisfied.